2020
DOI: 10.1002/app.48937
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of amino‐functionalized polyphosphazene microspheres and their application for highly sensitive fluorescence detection of Fe3+

Abstract: Amino-functionalized highly crosslinked organic-inorganic hybrid polyphosphazene microspheres were prepared via a one-pot polycondensation method and served as a fluorescent sensor for the detection of Fe 3+ in solution. With the introduction of p-phenylenediamine unites, the polyphosphazene microspheres could be endowed with fluorescent property and abundant active amino groups on the surface. The microspheres were further used as the fluorescent sensor for the detection of Fe 3+ . Fluorescence study showed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…The sensitivity of the polymer is comparable with previous reports; however, its detection range is higher than most of the reported ranges [ 37 , 41 , 42 ]. For example, Chen et al reported that the synthesis of polyphosphazene microspheres has selectivity for Fe 3+ aqueous solutions and a detection limit of 76 × 10 −9 M (0.076 μM) in a range from 0 to 10 μM [ 37 ].…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…The sensitivity of the polymer is comparable with previous reports; however, its detection range is higher than most of the reported ranges [ 37 , 41 , 42 ]. For example, Chen et al reported that the synthesis of polyphosphazene microspheres has selectivity for Fe 3+ aqueous solutions and a detection limit of 76 × 10 −9 M (0.076 μM) in a range from 0 to 10 μM [ 37 ].…”
Section: Resultssupporting
confidence: 87%
“…The sensitivity of the polymer is comparable with previous reports; however, its detection range is higher than most of the reported ranges [37,41,42]. For example, Chen et al reported that the synthesis of polyphosphazene microspheres has selectivity for Fe 3+ aqueous solutions and a detection limit of 76 × 10 −9 M (0.076 μM) in a range from 0 to 10 μM [37]. Additionally, Yang et al reports sensitivity for Fe 3+ in N, N dimethylformamide The sensitivity of the polymer is comparable with previous reports; however, its detection range is higher than most of the reported ranges [37,41,42].…”
Section: Photoluminescence Properties Of Poly(ani-amps)supporting
confidence: 88%
See 3 more Smart Citations